O impacto distributivo do salário mínimo: a distribuição individual dos rendimentos do trabalho - Soares, Sergei Suarez Dillon (Economia Aplicada, 2004)
The objective of this paper is to estimate the impact that changes in the value of the minimum wage will have upon the distribution of individual labor income. Two complementary approaches will be used. The first approach is to use non-parametric methods to estimate the individual income labor distribution. The estimator used is the kernel estimator and the data come from the five PNADs since the Real Plan. The next approach in the paper is quantify the elasticity of labor income with relation to minimum wage increases. The data come from the monthly PMEs since the Real Plan and the methodology is to use various comparison groups to net out the minimum wage effect.